The improvement of the final year of a university degree from production entities (Revision) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The paper is oriented to solve one of the problems that are manifested in the process of early job placement that occurs in the students of the final years of the different university careers in Cuba in the production and services entities, it responds to the research project: "The technological-pedagogical integration (INTECPED): a challenge of the training process of the professional. Its objective is expressed in providing a system of actions for the improvement of the final year of a university career from the production and services entities from premises that favor the systematization of the professional content from the invariants and organizational forms of the labor practice of the final year of a university career.
Keywords: labor practice; labor entity; university-labor entity integration